SPIA Ethiopia Report 2024: Building Resilience to Shocks - Alemu, Solomon; Ambel, Alemayehu; Khanal, Amit; Kosmowski, Frederic; Stevenson, James R.; Taye, Lemi; Tsegay, Asmelash; Macours, Karen (2024)
Since the first SPIA country study report on Ethiopia (Shining a Brighter Light: Comprehensive Evidence on Adoption and Diffusion of CGIAR-Related Innovations in Ethiopia (Kosmowski, F., et al., 2020)) the country has experienced a protracted civil conflict, repeated years of drought, a food security crisis, and the disruptions and shock of the COVID-19 pandemic. In this new report, we provide a unique national-level panel data perspective on the dynamic changes in the reach of agricultural innovations during these challenging times, leveraging the same nationally representative survey approach as we used in the 2020 report. This allows us to look at changes in the adoption and diffusion of agricultural innovations over the period 2018/19 to 2021/22.